Increasing Seismic Energy Dissipation of Steel Moment Frames Using Reduced Web Section (RWS) Connection. Issue 7 (3rd October 2017) - Erfani, Saeed; Akrami, Vahid
Abstract : Connections of steel moment frames are vulnerable to brittle failure. Providing a perforation near the beam-ends is suggested as a potential method to improve seismic behavior of these structures. This article presents a numerical study on the energy dissipation of steel moment connections with perforated beam. Models with elongated circular openings of different dimensions and location are analyzed and compared based on the global and local damage indices, predicted failure time and dissipated energy. Results show that an RWS connection with a proper opening size can develop reasonable inelastic deformations and provide an acceptable seismic improvement to moment-resisting frames.